Structural change in agriculture and rural livelihoods: Policy implications for the New Member States of the European Union - Judith Möllers; Gertrud Buchenrieder; Csaba Csáki (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Table of Contents: Gertrud Buchenrieder and Judith Möllers, The transformation of the rural economy in the new member states of the European Union: Implications for empirical analyses of rural structural change and livelihoods ... 1; Luka Juvančič and Tina Jaklič, Recent trends, drivers and impacts of structural change in agriculture ... 37; Carmen Hubbard and Matthew Gorton, Lessons from established member states: translating good practices to the new member states ... 61; Johan F.M. Swinnen and Kristine Van Herck, A comparative analysis of rural labour markets ... 83; Judith Möllers, Gertrud Buchenrieder, Diana Traikova, Thomas Dufhues, Jana Fritzsch, and Cosmin Salasan, Rural livelihoods in transition: structural change beyond agriculture ... 109; Sophia Davidova, Lena Fredriksson and Alastair Bailey1,Rural livelihoods in transition: market integration versus subsistence farming ... 131; Dominika Milczarek-Andrzejewska, Tomasz Wołek, and Beata Łopaciuk- Gonczaryk, The role of social capital and informal cooperation: market Integration of farms in Poland ... 159; Hauke J. Schnicke1, The impact of demographic patterns in Hungarian farm households on structural change ... 181; Csaba Csáki and Attila Jámbor, Policy conclusions and recommendations ... 211
urn:nbn:de:gbv:3:2-18711
Keywords: 330